O-Arm-Navigated, Robot-Assisted Versus Conventional CT Guided Radiofrequency Ablation in Treatment of Osteoid Osteoma: A Retrospective Cohort Study - Wang, Tian-Long; Luo, Yi-Ping; Zhou, Zi-Fei; Liu, Jun-Feng; Hou, Xiao-Dong; Jia, Shao-Hua; Zheng, Long-Po (Frontiers in Surgery, 2022)
Background Osteoid osteoma is a common benign bone tumor and clinically there is severe local pain and typically worse at night. The conventional CT-guided radiofrequency ablation was widely used in the treatment of osteoid osteoma, which may result in some radiation-related and imprecise complications for the overdose of radiation exposure. This study aimed to compare the surgical effect of robot-assisted RFA with O-arm navigation and conventional CT-guided RFA in the treatment of osteoid osteoma (OO). Methods Sixty-two patients who underwent robot-assisted RFA with O-arm navigation (Robot-RFA, n=24) or CT-guided RFA (CT-RFA, n=38) were included in this retrospective cohort study. The mean follow-up time was 23.3 months. The intra-operative data, primary technical success rate, visual analog scale (VAS), and postoperative complications were analyzed. Results Primary technical success was obtained in 23 patients who had robot-assisted RFA, and 35 patients who had conventional CT-guided RFA. One patient in the Robot-RFA group and three patients in the CT-RFA group with pain recurrence received repeat-RFA and had a secondary success. Mean operation time, the dose of radiation exposure were less in the Robot-RFA group than that in the CT-RFA group. The Robot-RFA group took fewer K-wire adjustment times for each patient than the CT-RFA group. There was a statistically significant difference in the mean operation time, the dose of radiation exposure, and K-wire adjustment times between the groups (p < 0.05). No complications associated with the procedure were reported in the two groups during the follow-up period. Conclusion Robot-assisted RFA with O-arm navigation is a safer and more precise strategy in the treatment of osteoid osteoma with less operation time and radiation exposure compared with the conventional CT-guided radiofrequency ablation.